An Innovative Application On Supermarket Selection Through Using Intuitionistic Fuzzy TOPSIS Method - Feride Tuğrul (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi, 2022)
Multi-criteria decision making methods have recently attracted the attention of researchers and have had a large share in multidisciplinary fields. In this study, using the intuitionistic fuzzy TOPSIS method, supermarket chains were evaluated in the consumer context and the most preferred supermarket was determined. Consumers' opinions were expressed using linguistic term. The reason why the intuitionistic fuzzy TOPSIS method is preferred; it is the ability of consumers to express their opinions easily, to take into account the undecided situations with the help of intuitionistic fuzzy sets, and thus to create an objective decision making mechanism.